Teoria e prassi del personaggio nel Nouveau Roman (ENTHYMEMA, 2020)
The paper proposes some general considerations about the literary character’s mechanisms of emotional identification exemplified in the work of Nathalie Sarraute and Alain Robbe-Grillet with a subsequent reference to the Nouveau Roman poetics. The focus of the attention is placed on the differences between the two authors’ theoretical positions, aiming at highlighting the gap that this type of novelistic production engenders between programmatic authors intentions and the actual process of writing.